Applicability of an Osteogeometric Method of Spheroid Human Bone Fragments (2016)
Introduction: fragmented bone remains represent a challenge for bio-anthropo-logists and archeologists, as they are used to rebuild every anatomical or bone part to provide relevant information. As main study objective, it was established that by measuring the sagitta of a cap-preserved human femur, the diameter of the head is obtained, with the purpose of establishing the sex of the individual with his/her probable height. Methodology: this was done by using a geometric relationship based on the Pythagorean theorem and an adaptation of a domestic spherometer to a sliding gauge. 35 left femurs of 10 women and 25 men were used from a total of 149 cases available at the National Institute of Legal Medicine and Forensic Sciences, Meta Branch in Villavicencio, Colombia from 2015 to 2016. Results: It was possible to demonstrate that there is an association between the sagitta of the cap and the femoral diameter (r2 = 0.87; p value = 0.05), with values lower than those reported in foreign literature for diameters of femoral heads and where it was possible to establish gender by knowing the sagitta. Conclusions: This study could be the main source of information on similar work in an area of the country where the discovery of incomplete, but explorable human remains is common.